2008
DOI: 10.1007/s11207-008-9142-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Wave Motion in Inclined Magnetic Fields within Sunspot Penumbrae

Abstract: At the surface of the Sun, acoustic waves appear to be affected by the presence of strong magnetic fields in active regions. We explore the possibility that the inclined magnetic field in sunspot penumbrae may convert primarily vertically-propagating acoustic waves into elliptical motion. We use helioseismic holography to measure the modulus and phase of the correlation between incoming acoustic waves and the local surface motion within two sunspots. These correlations are modeled by assuming the surface motio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The field inclination is also mixed within the vicinity of seismic sources, with the inclined field seen throughout the active region, but with more significant changes seen in regions 1-4 during the scan covering the time of the flare. This can be important for the generation of helio- since mode conversion will occur more effectively when the sound and Alfvén speeds coincide (Cally 2000;Schunker et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The field inclination is also mixed within the vicinity of seismic sources, with the inclined field seen throughout the active region, but with more significant changes seen in regions 1-4 during the scan covering the time of the flare. This can be important for the generation of helio- since mode conversion will occur more effectively when the sound and Alfvén speeds coincide (Cally 2000;Schunker et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Schunker et al (2008) explored the wave motions with the presence of inclined magnetic field inside sunspot penumbra, and Felipe, Khomenko, and Collados (2010) discussed the wave mode conversions in the magnetized plasma by using 3D MHD simulations. More recently, Kitiashvili et al (2011) showed through MHD simulations that vertical magnetic field would introduce some acoustic frequency shifts toward higher frequency, but an inclined magnetic field would shift the frequency more substantially.…”
Section: Implications For Sunspot Subsurface Structurementioning
confidence: 99%
“…For example, Cally et al (2003) investigated mode-conversion mechanism in inclined fields and reproduced the observed phase shifts calculated from Hankel analysis by Braun (1995). Recently, Lindsey & Braun (2005) and Schunker et al (2008) have shown that the phase shift of the outward propagating waves is opposite to the phase shift of the inward propagating waves in stronger, vertical fields. Couvidat & Rajaguru (2007) also report possible contamination of helioseismic inversions for sound speed beneath sunspots, possibly due to near surface magnetic field effects.…”
Section: Discussionmentioning
confidence: 69%
“…Although this ratio cannot be currently measured accurately from observations, one can constrain it for this model by surface observations of the vector magnetic field of sunspots (see e.g. Schunker et al 2008). Thus we expect typical value of D/R to be 0.4 < D/R < 2 for the inclination observed in the sunspots between umbrae and penumbrae.…”
Section: Discussionmentioning
confidence: 99%